Screening of Coulomb interactions in liquid dielectrics. (28th May 2019) - Seyedi, Salman; Martin, Daniel R; Matyushov, Dmitry V
Abstract: The interaction of charges in dielectric materials is screened by the dielectric constant of the bulk dielectric. In dielectric theories, screening is assigned to surface charges appearing from preferential orientations of dipoles along the local field in the interface. For liquid dielectrics, such interfacial orientations are affected by the interfacial structure characterized by a separate interfacial dipolar susceptibility. We argue that dielectric properties of polar liquids should be characterized by two distinct susceptibilities responsible for local response (solvation) and long-range response (dielectric screening). A microscopic model for dipolar screening in polar liquids is developed here. It shows that the standard bulk dielectric constant is responsible for screening at large distances. The potential of mean force between ions in polar liquids becomes oscillatory at short distances. Oscillations arise from the coupling of collective longitudinal excitations (dipolarons) of the polar liquid with its interfacial density profile. Interfacial electrostatics demonstrates a crossover beyond the solute radius of ̃1 nm from the scaling laws roughly consistent with continuum expectations for small solutes to new scaling trends characterizing the much softer nano-scale solute–solvent interface. This crossover also marks the transition to a continuum-type electrostatic screening between ions, when short-distance oscillation of the potential of mean force become strongly damped. Screening oscillations are enhanced for more structured interfaces.